Public management information systems - Rocheleau, Bruce A. (Idea Group, 2006)
"This book focuses on the key processes faced by managers in governmental organizations, including planning, purchasing, training and learning, politics, accountability, ethics, best practices, and evaluation"--Provided by publisher.